PENGEMBANGAN MEDIA VIDEO EDUKASI GIZI SEIMBANG SEBAGAI UPAYA DALAM PENCEGAHAN PENYAKIT TIDAK MENULAR PADA REMAJA - Mahmudah, Umi; Priawantiputri, Witri (Poltekkes Kemenkes Bandung, 2024)
Teenagers are a group vulnerable to obesity. Obesity is one of the main causes of non-communicable diseases (NCDs). Diet is the most influential risk factor for obesity. Nutrition education is one way to prevent obesity. Educational media is the key to the success of nutrition education. Video is an audio-visual media that displays material that can provide students with real experiences. The research aimed to develop balanced nutrition video nutrition education media for teenagers and determine the suitability of nutrition education video media to be applied as educational media. This research was development research using steps (1)analysis: analyzing problems, needs, goals (2)design: making scripts and storyboards. (3)development: producing videos. (4)implementation: testing feasibility by media and material experts and teenagers in SMAN 1 Cimahi has 30 students as a potential user, review, revision. (5)evaluation: evaluate the results, and carry out revisions. The research results obtained 2 series of animated videos, namely series 1 regarding prevention of non-communicable diseases and series 2 regarding balanced nutrition. The average validation results on animated video 1 by media experts were 95.26%, material were experts 87.85%, while the average validation results on animated video two by media experts were 92.26%, material experts 92.14%. The validation results by material experts and media experts on animated video series 1 and 2 were declared very valid. The results of student trials as users showed that animated video media 1 and 2 can be well received by potential users. The animated video media series 1 and 2 can be used as media for nutrition education, especially for teenagers.